2011
DOI: 10.5152/tjh.2011.06
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and tumor lysis syndrome in children with non-Hodgkin’s lymphoma and acute lymphoblastic leukemia

Abstract: Objective: This study aimed to examine the incidence, clinical characteristics, and outcome of hyperuricemia and tumor lysis syndrome (TLS) in children with non-Hodgkin's lymphoma (NHL) and acute lymphoblastic leukemia (ALL). Materials and Methods: This retrospective study included data from 327 patients (113 NHL and 214 ALL). Results: Hyperuricemia occurred in 26.5% and 12.6% of the patients with NHL and ALL, respectively. The corresponding figures for TLS were 15.9% and 0.47% (p=0.001). All hyperuricemic NHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…The incidence of hyperuricemia in this study was 23% before treatment and 21.3% after treatment. The result shows that the patients have already developed hyperuricemia before treatment which is in agreement with a result reported from a retrospective study in Turkey which showed a hyperuricemia of 26.5% [ 6 ]. But our result is not in agreement with a 40% hyperuricemia, reported from a descriptive study conducted at Liaquat [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The incidence of hyperuricemia in this study was 23% before treatment and 21.3% after treatment. The result shows that the patients have already developed hyperuricemia before treatment which is in agreement with a result reported from a retrospective study in Turkey which showed a hyperuricemia of 26.5% [ 6 ]. But our result is not in agreement with a 40% hyperuricemia, reported from a descriptive study conducted at Liaquat [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…CTLS is defined as LTLS accompanied by one or more clinical manifestations such as cardiac arrhythmia, AKI, seizure, or death with an elevated serum creatinine > 1.5ULN (upper limit of normal) [ 6 ]. TLS is the mainstay for the complication and unfavorable outcome of cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In a multicenter cohort study of 153 high-risk patients with acute leukemia, aggressive NHL, and Burkitt leukemia/lymphoma, the overall incidence of TLS was found to be 30.7% [ 32 ]. Sevinir et al reviewed medical records of 327 children with NHL and ALL retrospectively and reported overall 5.8% incidence of TLS and an incidence of 15.9 % and 0.47% in NHL and ALL, respectively [ 40 ]. In another review of 398 children diagnosed with ALL conducted by Al Bagshi et al, the TLS incidence of 19% has been reported based on Hande and Garrow definitions [ 12 ].…”
Section: Incidence Of Tumor Lysis Syndrome In Hematological Malignmentioning
confidence: 99%
“…In addition, cell lysis occurs during treatment with chemotherapy or cytoreductive agents not only can aggravate elevated serum uric acid (SUA) but also increase urine uric acid (UUA) excretion and acute uric acid nephropathy is possibly anticipated. Therefore, it is generally suggested that allopurinol should be prescribed in these patients to prevent acute uric acid nephropathy (1)(2)(3)(4). Moreover, hyperuricemia has welldescribed reports on the association with physical illnesses such as hypertension, impaired fasting blood glucose and type 2 diabetes, metabolic syndrome, and coronary heart disease in previous studies (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 98%